Culture Diversity in Urdu Novel (With Reference to the Special Pakistani Female Novelist) - Noshair, Kinza; Razzaq, Noreen (sourcecoder, 2022)
The novel expresses the ground realities and cultural activities of its time. The novelist derives his themes from life and society. These themes paint a picture of their era that reflects civilization and culture. Man cannot live without civilization and civilization cannot come into existence without man. In the drains of Pakistani women novelists, there is a mixture of Pakistani culture, Indian culture and mixed culture. Pakistani culture in which dance and music festivals, customs, literature, religion, art, fine arts, architecture, eating and drinking etiquette, nisht and barkha and traditions are deeply rooted. Seem to be intertwined in civilization and culture.